x - 5
Without values for x, you cannot get an answer and it cannot be further simplified, so it will stay as: x² - 8x + 15
8x squared
The given expression can be simplified to: 8x squared +9
(x-3)(x-5) = 0
x + 3
x - 3
x - 5
X2 - 8X + 15 = (X - 3)(X - 5)
Without values for x, you cannot get an answer and it cannot be further simplified, so it will stay as: x² - 8x + 15
(x - 5)(x - 3)
8x squared
It is: 25+64 = 89
The given expression can be simplified to: 8x squared +9
(x-3)(x-5) = 0
(5x 2 - 8x + 1) + (2x 2 - 4x - 11)
4